Pelatihan Digital Marketing Media Pemasaran Madu dalam Meningkatkan Perekonomian Masyarakat Kampung Baru - Ina Namora Putri Siregar; Devi Alvionita Alindra; Winda Sri Astuti Doloksaribu; Maisara Batubara; Lasma Ria Tampubolon; Esther Praja (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
Marketing techniques are now developing very rapidly, these marketing techniques are now called Digital Marketing. Digital Marketing has increased and has begun to compete with the existence of traditional marketing techniques. Digital marketing is considered more effective because it can reach a wider market and allows anyone to access and obtain information and carry out the buying and selling process more easily. This Sharing Session and digital marketing training in an effort to develop local products through social media networks aims to train honey small business players in Kampung Baru Village, Medan Maimun District, in maximizing the marketing of honey products. The stages of this activity are the preparation stage and the training stage as well as the Sharing Session. The result of this activity is that business actors obtain information about the usefulness of various features in the WhatsApp Business application and Facebook Marketplace, the use of advertising language, and product distribution techniques.